Digitalisation of Birth Registration System in Malaysia: Boon or Bane for the Hard-to-reach And Marginalised? - Rodziana Mohamed Razali; Tamara Joan Duraisingam; Nessa Ni Xuan Lee (Elsevier, 2024)
Indexed by Scopus